Brand Promotion: The Effects of Celebrity Endorsement and Brand Image on Consumer Buying Decision - Adinda Nur Annissa; Eristia Lidia Paramita (Jurnal Bisnis dan Manajemen, 2021)
In the recent years, the influence of celebrity in promoting a brand is promising. Without a doubt, celebrity endorsement will boost business brand awareness with an endorsement. This research objective is to analyse the effect of celebrity endorsement and brand image toward the customer buying decision. The purpose of this study is to provide guidance for both the brand and celebrities regarding to endorsing. The population was the consumer of Maybelline in Indonesia. Purposive sampling was used in this research with 216 respondent. Multiple regression analysis method was used in this research. This research implies that celebrity endorsement and brand image affected the customer buying decision and the result is that Celebrity Endorsement and Brand Image of Maybelline have a positive significant influence on the buying decision.